Population abundance of Aedes albopictus and culex quinquefasciatus in 24 hours cycle in residential areas, penang using different trapping methods - Wan Fatma Zuharah,; Aminoddin Sumayyah, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
The increasing concern on the current activity of Aedes albopictus and Culex quinquefasciatus mosquitoes as pest and diseases vector in the residential areas require thorough and immediate evaluation. Therefore, 24 hours trapping was conducted at the urban Sungai Dua and sub-urban Batu Maung residence area, Penang, Malaysia, using two different traps; BG- Sentinel Trap and CDC Fay-Prince Light Trap under two different light conditions to investigate the possibility effect of light to both mosquito species. CDC Fay-Prince light trap was effective in trapping Cx. quinquefasciatus than BG–Sentinel traps. The results indicated that both traps were ineffective to capture Ae. albopictus. In this study, the peak activity of Ae. albopictus was not following the diel host-seeking activity which this species active at daylight (6:00am–8:00am) and during night time (6:00pm–8:00pm). Whereas, Cx. quinquefasctus was captured mostly during the nocturnal time (12:00am–6:00am) with a greater number of Cx. quinquefasciatus mosquitoes captured under no light conditions. Meteorological parameter recorded within experiment such as temperature, relative humidity, and wind speed did not correlate with the abundance of both mosquito species (p> 0.05). However, light intensity parameters significantly affected Cx. quinquefasciatus mosquito abundance in both residential areas (p= 0.002), but not the Ae. albopictus mosquitoes (p= 0.086 Sungai Dua; p= 0.803 Batu Maung) as light is not a primary cue attraction factor to any host source towards this species. Ovitraps seem to be better tools for collecting and surveillance population of Ae. albopictus mosquitoes as compared to BG- Sentinel trap (Paired t-test; p= 0.019) and CDC Fay-Prince light trap (Paired t-test; p= 0.025). As a conclusion, BG-Sentinel trap and CDC Fay-Prince light traps is a not suitable tool for monitoring the activities of Ae. albopictus in the residential area, but CDC Fay-Prince light traps still found effective to use to capture Cx. quinquefasciatus. This study has therefore established immature sampling as the most effective method of capturing Ae. albopictus in a residential area.